2004
DOI: 10.1002/jcb.20072
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer cell adhesion in response to Src kinase activation and actin‐cytoskeleton by non‐laminar shear stress

Abstract: Malignant cells shed from tumors during surgical resection or spontaneous metastasis experience physical forces such as shear stress and turbulence within the peritoneal cavity during irrigation, laparoscopic air insufflation, or surgical manipulation, and within the venous or lymphatic system. Since physical forces can activate intracellular signals that modulate the biology of various cell types in vitro, we hypothesized that shear stress and turbulence might increase colon cancer cell adhesion to extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…FSS has also been shown to induce changes in the gene expression, cytoskeletal, and adhesive properties of both leukocytes and cancer cells [32][33][34][35]. Here we found that FSS-naïve carcinoma cells exhibited a greater loss of cell viability in the first one to two passages, comparable to that measured in primary cells, but in subsequent passages, cell loss moderated, producing a biphasic viability curve.…”
Section: Discussionsupporting
confidence: 60%
“…FSS has also been shown to induce changes in the gene expression, cytoskeletal, and adhesive properties of both leukocytes and cancer cells [32][33][34][35]. Here we found that FSS-naïve carcinoma cells exhibited a greater loss of cell viability in the first one to two passages, comparable to that measured in primary cells, but in subsequent passages, cell loss moderated, producing a biphasic viability curve.…”
Section: Discussionsupporting
confidence: 60%
“…We have previously reported that a pathophysiologically relevant (15 mmHg) increase in extracellular pressure stimulates colon cancer cell adhesion to matrix proteins, endothelial cell monolayers, and surgical wounds in vivo by a ␤ 1 -integrin-dependent mechanism (2,58,64). Nonlaminar shear has a similar effect (61). Pressure stimulates cell adhesion to collagen, fibronectin, laminin, and Matrigel (2,26), suggesting that this effect is not restricted to a specific ␣/␤ 1 -integrin heterodimer pair.…”
mentioning
confidence: 94%
“…At least one pathway by which this occurs seems to involve focal adhesion kinase (FAK) and Src activation (2) and paxillin (6,7) and has been shown to be active in breast (8), head and neck (6), and colon (1) cancer cell lines, as well as in primary human colon cancer cells isolated directly from surgical specimens (2). These signals mediating increased adhesion are stimulated by increased extracellular pressure (2) as well as by laminar or nonlaminar shear stress (4,5,9).…”
Section: Introductionmentioning
confidence: 99%